Confirmation of Existing Insulin-like Growth Factor-1 Gene Associated with Growth and Milk-Production Traits and Genetic Diversity in Buffalo - Margawati, Endang Tri; Volkandari, Slamet Diah; Indriawati,; Thalib, Chalid (Makara Journal of Science, 2017)
Insulin-like growth factor-1 (IGF-1) gene plays an important role in the endocrine system of animals by regulating nutrient metabolism, growth, and milk production. There have been extensive molecular genetics research studies on cattle but less studies have focused on buffalo (Bubalus bubalis). This study aimed to confirm the association of IGF-1 gene in swamp or river buffalo (B. bubalis spp.) with growth and milk production traits. DNA samples were obtained from 12 buffalos (eight swamp buffalo and four river buffalo). One Bali cattle (Bos javanicus) was included as an outgroup (control). The eight swamp buffalo originated from East Nusa Tenggara (n = 1), Baluran, East Java (n = 4), and Banyuwangi, East Java (n = 3), while the four river buffalo originated from Sei Putih, Medan of North Sumatera. All DNA samples were amplified using an IGF-1 primer for 30 cycles, and amplicons were visualized on 1% agarose gel. Five of the 13 samples were sequenced to determine nucleotide sequence variation between the swamp and river buffalo. The results revealed that the size (225–231 bp) of all the fragments was in in accordance with that of IGF-1. There was not found genetic variation among the buffalo samples. The results indicate that buffalo samples bear growth and milk production traits.